2006
DOI: 10.1165/rcmb.2006-0012oc
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-Derived Elastase Induces TGF-β1 Secretion in Human Airway Smooth Muscle via NF-κB Pathway

Abstract: Neutrophils are infiltrated in airways of individuals with more severe and chronic asthma, with uncertain significance. Airway smooth muscle (ASM), apart from its contractile properties, is critically involved in the pathogenesis of asthma by producing inflammatory mediators. In the present study, we investigated the impact of neutrophil-derived elastase (NE) on ASM in terms of TGF-beta1 release, and we explored the underlying mechanisms. Primary ASM cells were serum starved for 24 h before stimulation with NE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
56
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 40 publications
(39 reference statements)
2
56
1
1
Order By: Relevance
“…In contrast to the comprehensive understanding of the NE-induced biological effect on respiratory epithelium, little is known about that on ASM. Previously, we have reported that NE also stimulates the TLR4/MyD88/TRAF6/NF-B pathway in primary human ASM (hASM) cells, leading to induction of TGF-␤1 transcription (17). However, despite NE activation of NF-B in hASM cells, NE was found to suppress the basal secretion of IL-8/CXCL8 in our preliminary study.…”
contrasting
confidence: 56%
See 1 more Smart Citation
“…In contrast to the comprehensive understanding of the NE-induced biological effect on respiratory epithelium, little is known about that on ASM. Previously, we have reported that NE also stimulates the TLR4/MyD88/TRAF6/NF-B pathway in primary human ASM (hASM) cells, leading to induction of TGF-␤1 transcription (17). However, despite NE activation of NF-B in hASM cells, NE was found to suppress the basal secretion of IL-8/CXCL8 in our preliminary study.…”
contrasting
confidence: 56%
“…In addition to its direct antibacterial effects, increasing evidence indicates that NE can provoke a variety of cellular responses in respiratory epithelial cells. By activating specific intracellular signal pathways, including NF-B, MAPK, and protein kinase C (13)(14)(15)(16)(17), NE induces expression of a number of genes, such as IL-8/CXCL8 (13,14,18), cathepsin B, matrix metalloprotease-2 (15), and MUC5AC (19). NE has been shown to activate NF-B through the TLR4/MyD88/ TRAF6 pathway, leading to induction of IL-8/CXCL8 expression in bronchial and lung epithelial cells (14,20,21).…”
mentioning
confidence: 99%
“…One of these, TGF-b, has a complex role in the pathogenesis of severe asthma (35). It is produced by several cell types, including epithelial cells, eosinophils, macrophages, fibroblasts, and helper T cells (36,37), and is involved in epithelial transformation, subepithelial fibrosis, airway smooth muscle remodeling, microvascular changes, mucus production, and both suppressing and activating inflammatory cytokines (38)(39)(40)(41). TGF-b 1 is a major regulator as well as effector in the immune response.…”
Section: C/fpomentioning
confidence: 99%
“…36 A similar mechanism of action may function in DCs, since we presently report that elastase and even PMN CS decrease IB␣ protein expression. The fact that pretreatment with SLPI prevented the PMN CS-induced IB␣ degradation further supports the role of elastase.…”
Section: Discussionmentioning
confidence: 74%
“…41 Interestingly, elastase has been shown to increase the release of TGF-␤1 by airway smooth muscle. 36 Furthermore, lung DCs have an immature phenotype. 42 Recently, Roghanian et al 43 showed that sputum from chronic obstructive pulmonary disease and patients with cystic fibrosis or elastase down-regulated the expression of CD40, CD80, CD86 (but not MHCII) on murine DCs, inhibited LPSinduced murine DC maturation and T-cell proliferation.…”
Section: Discussionmentioning
confidence: 99%